CLINICAL FEATURES OF SCARLET FEVER - Fakhriddinova Shahnoza Fakhriddinovna (World Scientific Research Journal, 2025)
Summary. Streptococcal infection remains one of the most pressing health problems in all countries, which is determined by the widespread prevalence of group A streptococci and the enormous socio-economic damage caused by this pathology.